ECONOMIC EFFECTS OF INTEGRATED MARKETING COMMUNICATIONS – THE CASE OF FOOD PRODUCTS - Đokić, Ines (Economics of Agriculture, 2018)
Integrated marketing communications (IMC) present a concept in which various instruments of promotion and media are combined into a consistent message, in order to achieve their synergetic effects observed through better communication and economic indicators. The aim of this paper is to explore the differences in the economic effects of integrated market communications between consumer segments defined on the basis of the number of integrated marketing communications instruments related to a particular product to which influences consumers are exposed as well as on the perception of a unique promotional message from all these instruments. The research was related to consumption of chocolate, coffee and bottled water in Serbia and included the total of 1000 respondents. The results generally show that consumers who are exposed to the integrated marketing communications in relation to a particular food product spend more on buying it and buy it more often.